G-protein involvement in muscarinic receptor-stimulation of inositol phosphates in longitudinal smooth muscle from the small intestine of the guinea-pig. - Prestwich, S A (1995)
1. Aluminium fluoride (AlF), pertussis toxin (PTX) and cholera toxin (ChTX) have been used to examine the involvement of G-proteins during muscarinic acetylcholine receptor (AChR) stimulation of inositol phospholipid hydrolysis in fragments of longitudinal smooth muscle from the small intestine of the guinea-pig. 2. Carbachol (CCh) induced time- and concentration-dependent increases in [3H]-inositol monophosphates, [3H]-inositol (1,4) bisphosphate, [3H]-inositol (1,3,4) trisphosphate, [3H]-inositol (1,4,5) trisphosphate ([3H]-Ins (1,4,5)P3) and [3H]-inositol tetrakisphosphates measured by h.p.l.c. These increases were inhibited > 95% in the presence of the muscarinic AChR antagonist atropine (0.5 microM). 3. AlF transiently increased the basal levels of [3H]-Ins (1,4,5)P3 but increases in the levels of the other [3H]-inositol phosphates occurred more slowly. CCh-induced increases in the levels of all the [3H]-inositol phosphates were strongly inhibited in the presence of AlF. 4. PTX had no effect on basal levels of any of the [3H]-inositol phosphates but reduced the effects of CCh on these; ChTX had no effects on either basal or CCh-stimulated levels. 5. It was concluded that muscarinic AChR-stimulated increases in the levels of [3H]-inositol phosphates occur via both a PTX-sensitive G-protein and a PTX-insensitive mechanism. The actions of AlF may suggest the involvement of an inhibitory G-protein in the regulation of muscarinic AChR-stimulated inositol phospholipid turnover.